The ever-running man - Muller, Marcia (Muller, Marcia. Sharon McCone mysteries., 2007)
"The history of corruption may jeopardize Sharon McCone's marriage, but uncovering the secrets of a mysterious firm may be the only way she can save her husband's life, and her own"--Provided by publisher.